Comparative Investigation of Physiological and Anticancer Properties of Gundelia tournefortii L. From Three Regions of Javanroud, Kermanshah (Iran) on HL-60 Cancer Cells - Yosra Sedighi; Maryam Rahimi; Masoumeh Maleki (Complementary Medicine Journal of Faculty of Nursing and Midwifery)
Introduction: Cancer is a disease that occurs due to uncontrollable cell division under the influence of genetic and environmental factors. Nowadays, various methods of chemotherapy and radiotherapy are used for treating different types of cancer, but they come with significant drawbacks. Since chemotherapeutic drugs are synthetic and have numerous side effects for patients, many researchers propose the use of natural extracts derived from plants. The present study aimed to conduct a comparative examination of the physiological and anticancer properties of Gundelia tournefortii L. plants harvested from three regions in Javanroud, Kermanshah (Iran) on HL-60 cancer cells. Methods: In the present study, information related to geographical location, annual precipitation, and weather characteristics was collected. Additionally, soil characteristics and physiological properties of plants were investigated. Then, an extract was made from the stem of the plant, and the effect of the extract with different concentrations on HL-60 cancer cells was studied using an MTT assay. Results: The results indicated that pH, EC, Ca, Mg, Na, and K were variable in the compared areas. Moreover, the amounts of chlorophyll A, Chlorophyll B, and carotenoid significantly differed in the three regions. However, anthocyanin, sugars, and phenol did not show considerable changes. Regarding the effect of plant extract on cancer cells, the results indicated that the plant extract extracted from the Ghori Qala and Khanumabad regions has a more substantial effect on killing cancer cells compared to the plant extract extracted from the Nahrab region. Conclusion: It seems that there are more anti-cancer compounds in the Ghori Qala and Khanumabad plants than in the Nahrab area.